A pilot study of wellness coaching for smoking cessation among individuals with mental illnesses. (2nd January 2023) - Gao, Ni; Solomon, Phyllis; Clay, Zakia; Swarbrick, Peggy
Abstract: Background: Smoking continues to be a major health concern among persons with mental illnesses. Aims: This pilot study compared smoking outcomes between wellness-coaching for smoking cessation and a control group. Methods: Thirty-one individuals were enrolled in an educational group on smoking cessation and 23 completed an eight-session manualized education. Following this educational group, 11 of 23 participants were randomly assigned to wellness coaching for four months and 12 to a control condition. ANCOVAs were used to compare group differences in smoking outcomes. Results: Fagerström Nicotine Dependence Index (FTND) score of the participants who received the wellness coaching intervention decreased significantly as compared to the control group, indicating a lower level of nicotine dependence. The outcomes of average number of cigarettes smoked daily and breath carbon monoxide level showed tendencies towards reductions for wellness coaching, although not statistically significant compared to the control condition. Conclusions: Suggestions are shared about the feasibility of wellness coaching as well as barriers and challenges learned in implementing such an intervention to assist individuals with mental illnesses in quitting or reducing smoking.